Effect of temperature and kinetic modelling of lignosulfonate adsorption onto powdered eggshell in batch systems - Muhammad Ali Zulfikar; Henry Setiyanto; Samitha Dewi Djajanti (Songklanakarin Journal of Science and Technology (SJST), 2013)
The sorption of lignosulfonate onto powdered eggshell under the influence of temperature has been studied. The rate of adsorption onto eggshell was investigated under a variety of adsorbent dosages. The kinetic data from these investigations were correlated to a number of adsorption models in an attempt to elucidate the mechanism of the adsorption processes. Thermodynamic parameter data indicated that the lignosulfonate sorption process was non-spontaneous and endothermic under the experimental conditions, with the Gibbs free energy (Go) in the range of 1.83-1.07 kJ mol-1, enthalpy (Ho) andentropy (So) of 5.66 kJ mol-1 and 12.82 J mol-1, respectively and the activation energy of 18.17 kJ mol-1. The adsorption mechanism was found to follow a pseudo-second-order model, with the kinetic constants in the range of 0.689–1.430 g mg-1 min-1. Both the intra-particle diffusion and Boyd kinetic models indicated that boundary layer/film diffusion was the main rate determining step in lignosulfonate adsorption process.